Determining Cochlear Implant Candidacy in Adults: Limitations, Expansions, and Opportunities for Improvement - Zwolan, Teresa A.; Basura, Gregory (Seminars in Hearing, 2021)
The safety, efficacy, and success of cochlear implants (CIs) are well established and have led to changes in criteria used by clinicians to determine who should receive a CI. Such changes in clinical decision-making have out-paced the slower-occurring changes that have taken place with regulatory bodies' and insurers' indications. We review the historical development of indications for CIs, including those of the U.S. Food and Drug Administration (FDA), Medicare, Medicaid, and private insurers. We report on expansion to include patients with greater residual hearing, such as those who receive Hybrid and EAS devices, and report on recent FDA approvals that place less emphasis on the patient's best-aided condition and greater emphasis on the ear to be treated. This includes expansion of CIs to patients with single-side deafness and asymmetric hearing loss. We review changes in the test materials used to determine candidacy, including transition from sentences in quiet to sentences in noise to the recent use of monosyllabic words and cognitive screening measures. Importantly, we discuss the recent trend to recommend CIs despite a patient not meeting FDA or insurers' indications (a practice known as “off-label”), which serves as attestation that current indications need to be updated.
Keywords: cochlear implant candidacy; indications; speech recognition; FDA approval